Analysis of the Contribution of the Agricultural Sector and the Fisheries Sector to the Economic Growth of West Java: Agricultural sector, Fisheries sector, West Java Economic Growth - Herman Kambono (Magister Akuntansi FB-UK.Maranatha, 2025)
This study aims to analyze the contribution of the agricultural sector and the fisheries sector to economic growth in West Java during the period 2008-2023. The data used are secondary data from the Central Statistics Agency (BPS). The analysis method uses multiple linear regression to test the relationship between independent variables (agricultural sector and fisheries sector) and the dependent variable (economic growth of West Java). The results of the study indicate that the agricultural sector has a positive and significant influence on the economic growth of West Java, with a significant contribution to increasing Gross Regional Domestic Product (GRDP). Conversely, the fisheries sector shows a negative but insignificant influence on economic growth. The dependence of the fisheries sector is greatly influenced by weather conditions and other challenges, causing its contribution to be less stable. In conclusion, the agricultural sector is the main pillar supporting economic growth in West Java, while the fisheries sector requires a better and more effective management strategy to increase its contribution to the economic growth of West Java